Modeling The Nonlinear Behaviour Of A Driven Varactor Resonator At Low Frequencies - Kalomiros, John A.; Stavrinides, Stavros G.; Miliou, Amalia N.; Özer, Mehmet; Bulat, Taner (İstanbul Kültür Üniversitesi Yayınları, 2006)
We monitor the theoretical response of an R-L-Varactor circuit by using Multisim 7.0, at a driving frequency f= 1MHz with high driving amphtudes. Atlow frequencies a bifurcation is observed, attributed to the large capacitance emerging from the carrier injection at reverse-bias breakdown. By inereasing driving amplitude we observe non-periodic trajectories with increasing chaotic content in a four dimensional state-space. At specific amplitudes we monitor two-dimensional tori where trajectories are periodic, like in a two-oscillatorssystem with commensurate frequencies. The scenario from quasi-periodocity to chaos is discussed by means of estabhshed tools, hke the circle map, Poincare cross sections, power and FFT spectra, correlation dimension and Kolmogorov entropy. Peak amphtudes of the monitored waveforms are shown to form an interesting pattem of well defined groups, within the resolution ofthe numerical solutions produced by the simulation.
Keywords: nonlinear; resonator; varactor; rezonatör; varaktör; doğrusal olmayan; low frequencies; düşük frekanslar